Common pool resource institutions: The rise of internet platforms in the social solidarity economy. (6th January 2021) - Ridley‐Duff, Rory; Bull, Mike
Abstract: The research problem: Theories of organising are dominated by a neoliberal agenda. This authority has been disrupted by social and sustainable entrepreneurship research that highlights alternatives to this hegemony. The motivation for this paper is to argue that the emergence of internet platforms contributes to new ways of working in the social solidarity economy (SSE). We focus our exploration on organisational practices and characteristics, evaluating platforms as contributions to commoning. Method: Our approach offers a way out of the public–private dichotomy. We build theory by positioning the SSE as a series of approaches that hybridise redistribution, reciprocity and market: three distinct strategies of social organisations for achieving their primary purposes. Utilising Elinor Oström's theory of common pool resource institutions (CPRIs) and her design principles, we appraise three internet platforms (Kiva, Loomio and Kickstarter). We triangulate organisational, academic and media narratives to assess the embeddedness of their commoning practices and potential as social innovations for a postcapitalist economy. Contribution to knowledge: Social enterprises (SEs) can develop internet platforms that use CBPP to build and support the SSE. This is the first paper to deploy Oström's work to study how SEs use CBPP, thereby developing the theoretical connections between these two fields. Our findings are part of a discourse that challenges neoliberalism and identifies how the SSE contributes to sustainable development.